A normative account of epistemic luck. Issue 1 (2nd September 2019) - Goldberg, Sanford C.
Abstract: This paper develops a normative account of epistemic luck, according to which the luckiness of epistemic luck is analyzed in terms of the expectations a subject is entitled to have when she satisfies the standards of epistemic justification. This account enables us to distinguish three types of epistemic luck—bad, good, and sheer—and to model the roles they play e.g. in Gettierization. One controversial aspect of the proposed account is that it is non‐reductive. While other approaches analyze epistemic luck in non‐epistemic terms—either in modal terms (lack of safety) or in agential terms (lack of creditworthiness)—I argue that the non‐reductive nature of the normative account is actually a selling‐point relative to its competitors.